Education On Child Protection Andthe Importance Of Education - Meisyara Cordelia Bintara Putri (PT. Berlian Pustaka Indonesia, 2023)
This research aims tocommunity members are more aware of child protection and are motivated to improve their standard of living by continuing their education to a higher level. The average knowledge of the community about the law is still low. Especially regarding the law on child protection, some don't even know anything about it. Many children are treated poorly, for example, children aged 6 years have worked hard to earn money. The number of cases of children being targeted or victims of crime is a very worrying problem for many parties. Violence against children also often occurs, where all forms of violence and exploitation of children will have a negative impact on physical and mental health that can interfere with the growth and development of children. This is also influenced by the lack of public knowledge about the importance of education and child protection. The data analysis used in this research is a field study, which is carried out using a direct survey method in Perbarakan Village, Pagar Merbau District, Deli Serdang Regency, North Sumatra and library research which is carried out in two ways, namely (1 ) Offline; namely collecting library research data directly in the library (both inside and outside the University of Muhammadiyah North Sumatra campus) in order to collect secondary data needed in research. (2) Online; namely library research which is carried out by searching through internet media in order to collect secondary data needed in research.